A cellulose acetate/Amygdalus pedunculata shell-derived activated carbon composite monolith for phenol adsorption. Issue 14 (16th February 2018) - Xiong, Qiancheng; Bai, Qiuhong; Li, Cong; He, Yuanyuan; Shen, Yehua; Uyama, Hiroshi
Abstract : In this study, we have developed a single-step method to fabricate a cellulose acetate (CA)/APS-derived activated carbon (AC) composite monolith by thermally induced phase separation (TIPS) for removal of toxic phenol from aqueous solution. Abstract : Amygdalus pedunculata is expected to be a good candidate plant for desert reclamation ("greening") since it has notable tolerance to cold and drought and can grow in a wide range of areas with different soil types and moisture contents. In this study, we have developed a single-step method to fabricate a cellulose acetate (CA)/ A. pedunculata shell (APS)-derived activated carbon (AC) composite monolith by thermally induced phase separation (TIPS) for removal of toxic phenol from aqueous solution. The composite monolith was easily fabricated by TIPS of a CA solution in the presence of the dispersed AC, in which AC was well loaded onto the monolithic skeleton of CA. The as-obtained monolith showed a maximum adsorption capacity of 45 mg g −1 at the initial phenol concentration of 0.8 mg mL −1 . The present composite can be prepared with an arbitrary shape by a facile method from cheap materials, and is more convenient to recycle than powder adsorbents. Therefore, the present CA/APS-derived AC composite monolith has great potential as a promising adsorbent of low cost with convenient separation for toxic phenol-containing wastewater.